Kajian Yuridis terhadap Upaya Preventif Memerangi Tindak Pidana Korupsi dalam Perspektif Hukum Administrasi Negara - Eki Rolando; Della Putri Ramadhani; Helda Helda; Putri Safira Apriadi; Rahma Fitri (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
In accordance with the mandate of the rule of law, Indonesia has always sought to remain guided by the law as an instrument to realise the original ideals of the nation. We know that Administrative Law is a branch of law that serves to regulate the correlation between the state (in this case, the government) and its citizens. The role of Administration Law becomes one of the pillar guidelines used to always ensure consistency between government action and law in order to be able to perform its functions optimally. However, one of the obstacles that remains the focus of the issue of government organisation is the punishment of corruption by government officials. For that, the primary purpose of this writing is to know further how the efforts to prevent criminal proceedings of corruption in the perspective of the Administrative Law. This article uses normative juridical research methods with qualitative analysis or library study. The material is obtained from reference sources of reading literature that still have relevance to the object of this research. The findings will be analysed and organised systematically in writing in the form of reading descriptions.